2019
DOI: 10.1177/1747493019830595
|View full text |Cite
|
Sign up to set email alerts
|

Hypoperfusion in lenticulostriate arteries territory related to unexplained early neurological deterioration after intravenous thrombolysis

Abstract: Background: Early neurological deterioration occurs in approximately 10% acute ischemic stroke patients after thrombolysis. Over half of the early neurological deterioration occurred without known causes and is called unexplained early neurological deterioration. Aims: We aimed to explore the development of early neurological deterioration at 24 h after thrombolysis, and whether it could be predicted by the presence of baseline hypoperfusion in lenticulostriate arteries territory in acute ischemic stroke patie… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
14
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 15 publications
(16 citation statements)
references
References 14 publications
2
14
0
Order By: Relevance
“…To prove the association of BPV and END, we adopted a definition of END as a ≥1‐point increase in NIHSS score during the first 72 hours after admission. And, the rate of END was 32.5% in this study, which was consistent with the rates in previous studies . And also, our findings were similar to that in the Chungs' study .…”
Section: Discussionsupporting
confidence: 92%
See 3 more Smart Citations
“…To prove the association of BPV and END, we adopted a definition of END as a ≥1‐point increase in NIHSS score during the first 72 hours after admission. And, the rate of END was 32.5% in this study, which was consistent with the rates in previous studies . And also, our findings were similar to that in the Chungs' study .…”
Section: Discussionsupporting
confidence: 92%
“…And, the rate of END was 32.5% in this study, which was consistent with the rates in previous studies. [4][5][6][7][8][9][10] And also, our findings were similar to that in the Chungs' study. 16 Both studies suggested that the acute in-hospital BPV was strongly associated with the risk of having a END.…”
Section: Discussionsupporting
confidence: 89%
See 2 more Smart Citations
“…Further analysis from our data demonstrated that minor non-disabling stroke with severe stenosis/occlusion could benefit from alteplase-treatment. Neurological deterioration commonly occurred in patients with severe stenosis of large vessels [ 11 , 18 , 19 ] It was reported that patients with mild deficits (NIHSS ≤ 5) and large vessel occlusion deteriorated more often in non-thrombolyzed patients than thrombolyzed patients within 3 months after onset [ 20 ]. Meanwhile, the NIHSS score was unable to exactly reflect the presence of intracranial artery occlusion.…”
Section: Discussionmentioning
confidence: 99%